2012
DOI: 10.1016/j.jadohealth.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Unprotected Sex in Shanghai, China: Correlates of Condom Use and Contraceptive Consistency Across Migrant and Nonmigrant Youth

Abstract: Purpose Despite the exceptionally large population of young migrants in China, as well as increasing rates of HIV and STIs in recent years, condom use and contraceptive consistency among this population remains critically under studied. This study examines the association between migration and condom use and contraceptive consistency. Methods A cross-sectional survey of 959 youth aged 15–24 was conducted in rural and urban Shanghai. Logistic regression was conducted to examine the association between migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…A potential explanation for this age-related trend might be that in this population, young adults more commonly work for long periods outside the rural home area than do older adults (data not shown), and the increased mobility might be associated with more unprotected sexual behavior and consequent increased exposure to HPV ( 10 ). …”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation for this age-related trend might be that in this population, young adults more commonly work for long periods outside the rural home area than do older adults (data not shown), and the increased mobility might be associated with more unprotected sexual behavior and consequent increased exposure to HPV ( 10 ). …”
Section: Discussionmentioning
confidence: 99%
“…Compared to other countries, the prevalence reported here is lower than among pregnant women in rural low-income settings in sub-Saharan Africa and Haiti [22][30] but higher than among women in rural areas in high-income countries like the U.S. [31] The syphilis epidemic among pregnant women in rural Guangdong province might be partially explained by female migrants or their husbands returning to their rural origins from the cities with untreated syphilis and persistently risky sexual behavior [32]. Studies have found that migrants in some Chinese cities have high-risk sexual behavior [33] and a higher prevalence of syphilis compared to local residents [16], [17], but few studies have examined the sexual risk of returning migrants.…”
Section: Discussionmentioning
confidence: 99%
“…Still, a growing body of literature suggests migrants are more likely to engage in high-risk behaviours, such as transactional sex . While there is limited data on the sexual-risk behaviours of 15 -24-year-old migrants in particular, studies have found that young migrants are more likely to participate in premarital sex (7.2 versus 4.5%), unprotected sex (47.3 versus 34.3%) and have earlier age of sexual initiation (Li et al 2009) and they are less likely to use condoms and use contraception consistently, compared to urban non-migrants (Sudhinaraset, Astone, and Blum 2012). Epidemiological studies document migrants' increased sexual risks, but less is known about the context of sexual risk among young migrants living in China.…”
Section: Introductionmentioning
confidence: 99%